Exfoliation of organically modified montmorillonite (O-MMT) nanofiller to enhance the performance of ethylene vinyl acetate (EVA) nanocomposites - Asna Rasyidah Abdul Hamid (School of Materials Engineering, 2019)
The study summarised in this thesis aimed at predicting and understanding the exfoliation behaviour of the organically modified montmorillonite (O-MMT) nanofiller upon the pre-dispersing technique to allow optimisation of EVA/O-MMT nanocomposite's mechanical and thermal properties. The four specific research objectives of this PhD project were:- to study the effects of dispersant concentration on thermal stability, structure and morphology of the pre-dispersed O-MMT prepared through magnetic stirring technique; to study the effects of dispersant concentration on thermal stability, structure and morphology of the pre-dispersed O-MMT prepared through the combination of magnetic stirring and ultra-sonication technique; to investigate the effects of pre-dispersing temperature and time on the thermal stability of the O-MMT pre-dispersed through the combination of magnetic stirring + ultrasonication techniques; to compare the morphology, structure, mechanical and thermal performance of the EVA/O-MMT nanocomposite incorporating the optimised pre-dispersed O-MMT nanofiller over the neat EVA and EVA/O-MMT (pristine) nanocomposite, when low and high nanofiller loadings are used.